Investing in skills for inclusive trade - Bacchetta, Marc; Gregg, Cornelius; Rubínová, Stela; Tumurchudur - Klok, Bolormaa (Geneva, 2017)
"In recent decades, the global economy has experienced a profound transformation due to trade integration and technological progress as well as important political changes. This transformation has been accompanied by significant positive effects at the global level, as increased trade integration has helped to raise incomes in advanced and developing economies, lifting millions out of poverty. At the same time, it has translated into changes experienced by individuals, companies and communities. While overall, better job opportunities are on the rise, workers who are forced to leave their existing jobs may find it difficult to share in these improvements.